0008 Impaired Post Illumination Pupil Response in Individuals with Delayed Sleep Wake Phase Disorder. (12th April 2019) - Choi, Jin Hyeuk; Abbott, Sabra M; Wilson, John; Zee, Phyllis C
Abstract: Introduction: Delayed sleep wake phase disorder (DSWPD) is characterized by a delayed sleep/wake cycle with respect to the external environment. Although it is the most commonly diagnosed circadian rhythm sleep wake disorder, its pathophysiology remains unclear. We tested the hypothesis that individuals with DSWPD have impaired phototransduction of their melanopsin containing intrinsically photosensitive retinal ganglion cells (ipRGCs) as measured by the post illumination pupil response (PIPR). Methods: Twenty-one individuals with DSWPD and 18 controls were recruited for the study. Subjects were screened via an eye exam and medical/sleep history interview by a board certified sleep physician. Reported rest-activity patterns were confirmed through two weeks of actigraphy and sleep log data. Subjects then underwent testing consisting of 5 minutes of dark accommodation followed by 30 seconds of blue light stimulus and 120 seconds of post illumination pupillary diameter recording using a pupillometer. This process was repeated afterwards with a red light stimulus. The PIPR was calculated by subtracting post illumination pupil diameter from baseline pupil diameter. Statistical differences between groups were predicted using unpaired t-tests. Results: Average sleep onset (3:36±0:26 (DSWPD) vs. 23:41 ± 0:41 (control)) and sleep offset (12:25±0:22 (DSWPD) vs. 7:45 ± 0:33 (control)) were significantly later in DSWPD subjects compared to controls. The PIPR to blue light was significantly smaller for DSWPD subjects compared with controls (0.97±0.18 mm vs. 2.12±0.26 mm, p<0.0005). There was no significant difference between groups when comparing the PIPR to red light (0.03±0.21 mm vs. 0.21±0.12 mm, p=0.46). Conclusion: One function of ipRGCs is to transduce photic input to the suprachiasmatic nucleus to entrain intrinsic circadian rhythms to external light cues. The decreased blue light PIPR in DSWPD subjects suggests that impairment of ipRGC phototransduction may have a role in the pathophysiology of this disorder. Support (If Any): American Sleep Medicine Foundation (award 155-JF-16) and the Northwestern Center for Circadian and Sleep Medicine.